(untitled) (Research, Society and Development, 2024)
This study aimed to assess the incidence of COVID-19 among dental students and their adherence to vaccination. From March 2020 to July 2023, the study was an observational, retrospective, cross-sectional, individualized survey involving students from all academic years of the undergraduate Dentistry course at an educational institution near Rio de Janeiro city, RJ, who willingly agreed to participate in the research. The questionnaire was distributed using Google Forms, with the first page including the Informed Consent Form for participation. Ninety-two questionnaires were completed, with 72.2% of respondents female, 58.7% aged 18-27 years, 64.1% single, and 87% working in clinical practices. Almost half of the participants (42.4%) reported being infected with COVID-19. As for vaccination adherence was notably high, with all participants (100%) receiving the first dose and 97.8% receiving the second dose. Most participants received the Pfizer vaccine for the first and second doses, followed by AstraZeneca. This high level of adherence to vaccination among the students is a testament to their dedication to their profession and the safety of their patients.